2019
DOI: 10.1016/j.kisu.2018.11.001
|View full text |Cite|
|
Sign up to set email alerts
|

China Kidney Disease Network (CK-NET) 2015 Annual Data Report

Abstract: Kidney International Supplements (2019) 9, e1-e81 e53 Chapter 6. Prevalence, incidence, and characteristics of dialysis patients e57 Chapter 7. Clinical measurement and treatment among dialysis patients e60 Chapter 8. Vascular access e62 Chapter 9. Cardiovascular diseases and diabetes among dialysis patients e63 Chapter 10. Hospitalization e66 Chapter 11. Medical expenditures for dialysis patients e68 Chapter 12. Kidney transplant waiting list e74 Chapter 13. Discussion e75 References e76 Appendices: Definitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
101
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 23 publications
0
101
0
Order By: Relevance
“…If inconsistencies are detected, the entire daily data package of the hospital will be rejected and the hospital will be required to review and resubmit. 15 The Chinese Stroke Center Alliance (CSCA) database is a national, hospital-based, voluntary, multifaceted intervention and continuous quality improvement initiative that provides a unique platform to develop stroke centres, improve stroke care quality and clinical outcomes. The CSCA was designed and led by a team of volunteers from the China Stroke Association under the guidance of the National Center for Healthcare Quality Management in Neurological Diseases.…”
Section: Continuedmentioning
confidence: 99%
“…If inconsistencies are detected, the entire daily data package of the hospital will be rejected and the hospital will be required to review and resubmit. 15 The Chinese Stroke Center Alliance (CSCA) database is a national, hospital-based, voluntary, multifaceted intervention and continuous quality improvement initiative that provides a unique platform to develop stroke centres, improve stroke care quality and clinical outcomes. The CSCA was designed and led by a team of volunteers from the China Stroke Association under the guidance of the National Center for Healthcare Quality Management in Neurological Diseases.…”
Section: Continuedmentioning
confidence: 99%
“…Patients undergoing maintenance hemodialysis (MHD) have abnormal immune systems because of the uremic state, 6 which is often accompanied by significant comorbidities like cardiovascular disease, diabetes, and cerebrovascular disease. 7,8 It would be interesting to know whether the clinical course of patients undergoing MHD having COVID-19 is different from that of other COVID-19 patients. Moreover, patients undergoing MHD in outpatient department must routinely visit the hospital and stay with dozens of patients undergoing MHD in a dialysis unit for 3-4 hours at a time, which may lead to widespread crosscontamination.…”
mentioning
confidence: 99%
“…A recent study analyzed the change in burden of CKD globally from 1990 to 2016 by using the Global Burden of Disease study data, the results showed that the incidence of CKD increased by 89%, prevalence increased by 87%, death due to CKD increased by 98% [3]. According to the data of a national epidemiological survey, it was estimated that the number of CKD patients in China was more than 100 million [6], and the number of patients receiving renal replacement therapy has increased rapidly in recent years [7]. There were about 553000 people received the hemodialysis and 55000 patients underwent peritoneal dialysis in 2015 [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to the data of a national epidemiological survey, it was estimated that the number of CKD patients in China was more than 100 million [6], and the number of patients receiving renal replacement therapy has increased rapidly in recent years [7]. There were about 553000 people received the hemodialysis and 55000 patients underwent peritoneal dialysis in 2015 [7]. It was estimated that the prevalence of CKD and end-stage renal disease (ESRD) would increase rapidly in the future [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation